Komunikace s dítětem s poruchou autistického spektra v nemocničním prostředí - Dobešová, Veronika; Glosová, Veronika; Botíková, Andrea; Bartoníčková, Daniela (Pediatrie pro praxi, 2023)
Communication impairment, which belongs to the basic triad of symptoms of autism spectrum disorder (ASD), can be a complication in providing comprehensive nursing care for children with this disorder. Nurses lack knowledge about the manifestations and issues of communication with children with ASD and often do not know how to establish effective communication. A short and clear form of communication is very important and sufficient time is needed. Short case studies revealed shortcomings in communicating with children with ASD in a hospital setting; communication with a child with ASD in a residential care facility could be an inspiration. From the available foreign resources, communication approaches and tools were selected, the knowledge and use of which in practice can contribute to improving the quality of nursing care for children with ASD.
Keywords: Communication; Nurse-Patient Relations; komunikace; Child, Preschool; Child; lidé; Female; Nurses; mužské pohlaví; Autism Spectrum Disorder; Male; dítě; předškolní dítě; vztahy mezi ošetřovatelkou a pacientem; zdravotní sestry; ženské pohlaví; poruchy autistického spektra; Humans